Sustainable Marketing in The Ready-Made Garments (RMG) Sector of Bangladesh - Mubina Khondkar; Salma Honey (Indonesian Journal of Social Research (IJSR), 2022)
Innovative managerial and social changes, such as sustainable marketing practices considerably improve organizational performance. Although the RMG sector of Bangladesh is widely known to global consumers through the ‘Made in Bangladesh’ tagline, effective implementation of sustainable marketing in the country has been proven as a difficult task. This research examines the current state and implications of sustainable marketing in the RMG sector of Bangladesh. Primary data were collected from 20 RMG factories located in Dhaka and Gazipur that were selected using convenience sampling techniques and 120 officials were selected using convenience and snowball sampling techniques. Data were analyzed using the content analysis technique where the theoretical framework was informed by the theory of planned behavior. The research shows that knowledge about sustainable marketing of most factories is limited and often they are not interested in practicing it. It also evidences that RMG manufacturers have been late in emphasizing and adopting sustainable marketing practices. They have not yet started showing concerns in this respect. Lack of supporting information systems often impedes the implementation of sustainable marketing practices. Legal requirements and the mandatory rule for sharing information regarding sustainable marketing work as the main motivations to adopt sustainable marketing practices.